STRATEGI DAKWAH KH. ACHMAD MUZAKKI SYAH PADA JAMA’AH PENGAJIAN DZIKIR MANAKIB - Djuwairiyah Djuwairiyah; Wisri Wisri (Maddah : Jurnal Komunikasi dan Konseling Islam, 2020)
Da'wah can also be called Islamic communication. In practice, da'wah is more interpreted as the delivery of Islamic teachings by a preacher. Sometimes preaching like this, more nuanced entertainment, so that afterwards does not cause a positive effect on the object of preaching. This is very different from the preaching done by KH. Achmad Muzakki Syah on the recitation of the recitation of the recitation of manakib Sheikh Abdul Qodir Jailani in PP. Al-Qodiri Jember. Where preaching, he can provide peace, accepted, and practiced by the object. The findings of this study are: First, the da'wah strategy is a therapeutic da'wah with the bi al-hikmah method and the bil thing method, namely by istiqamah praying for Muslims worldwide, fond of giving charity, and morality of the mercy, tahadduts bi an-ni'mah, utilizing family competence, and form the coordinator of the management. Second, the supporting factors of the da'wah strategy are family support, patient and forgiving personalities, high power, and strange events. While the inhibiting factor of the da'wah strategy is the emergence of slander that he uses the science of pellets, the help of jinn, and religious engineering